Alternative Sample Preparation Method for Large-Area Cross-Section View Observation of Lithium Ion Battery - 김지영; 정영우; 조혜영; 장혜정 (한국현미경학회, 2017)
Drastic development of ubiquitous devices requires more advanced batteries with high specific capacitance and high rate capability. Large-area microstructure characterization across the stacks of cathode, electrolyte and anode might reveal the origin of the instability or degradation of batteries upon cycling charge. In this study, sample preparation methods to observe the cross-section view of the electrodes for battery in SEM and several imaging tips are reviewed. For an accurate evaluation of the microstructure, ion milling which flats the surface uniformly is recommended. Pros and cons of cross-section polishing (CP) with Ar ion and focused ion beam (FIB) with Ga ion were compared. Additionally, a modified but new cross-section milling technique utilizing precision ion polishing system (PIPS) which can be an alternative method of CP is developed. This simple approach will make the researchers have more chances to prepare decent large-area cross-section electrode for batteries.